Hubungan personal hygiene dengan kecacingan pada anak SDN 149 Kecamatan Gandus Kota Palembang - Hermansyah, Herry; Damayanti, Dina Meilan; Yusneli (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2024)
Worm infestation is one of the diseases caused by Soil Transmitted Helminth (STH) infection, a group of worms that have a life cycle through the soil. Research Objective: To determine the relationship between personal hygiene and helminthiasis in SDN 149 GandusSubdistrict Palembang City 2024. Research Method: This study is Analytic ` with cross sectional. Research design : Results: From the results of the study obtained positive results 27.5% of children were contaminated with Soil Transmitted Helminth (STH) worm eggs with AscarisLumbricoides species. and there is a significant relationship between the frequency of habit of cutting , the habit of washing hands, the habit of using footwear p value 0.00, with helminthiasis. and in school facilities and infrastructure obtained invalid results because there is no measure of association calculated for cross tabulation between school facilities and infrastructure with the incidence of AscarisLumbricoides worm eggs in grades 1 and 2. Conclusion: From the results of this study it can be concluded that there are variables that have a significant relationship helminthiasis, among others, the frequency of habit of cutting nails, the habit of using footwear, the habit of washing hands, and in school facilities and infrastructure obtained invalid results because there is no measure of association calculated for cross tabulation between school facilities and infrastructure with the incidence of AscarisLumbricoides eggs in grades 1 and 2.